Historical notes on the training process of the comprehensive general doctor in Cuba - Beatriz Ramírez López (Centro Provincial de Información de Ciencias Médicas, 2022)
The Cuban public health is sustained in the Primary Health Care which improvement has been favored with the establishment of the comprehensive general medicine specialty in 1985, with substantial changes until the present time that have propitiated a step of important advance in the accessibility and quality in the medical services. Taking into account the above-mentioned the present study was carried out aimed at deepening in the historical tendencies that the training process of the comprehensive general doctor in Cuba has gone through. It was concluded that this process has had transformations that obey the national and international necessities, where all the versions of the program consider the education at work as main character in health services.